Non-sequential search, competition and price dispersion in retail electricity - Klaus Gugler; Sven Heim; Mario Liebensteiner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
We investigate the impact of consumer search and competition on pricing strategies in Germany's electricity retail. We utilize a unique panel dataset on spatially varying search requests at major online price comparison websites to construct a direct measure of search intensity and combine this information with zip code level data on electricity tariffs between 2011 and 2014. The paper stands out by explaining price dispersion by differing pricing strategies of former incumbents and entrant firms, which are distinct in their attributable shares in informed versus uninformed consumers. Our empirical results suggest causal evidence for an inverted U-shape effect of consumer search intensity on price dispersion in a clearinghouse environment as in Stahl (1989). The dispersion is caused by opposite pricing strategies of incumbents and entrants, with incumbents initially increasing and entrants initially decreasing tariffs as a reaction to more consumer search. We also find an inverted U-shape effect of competition on price dispersion, consistent with theoretical findings by Janssen and Moraga-González (2004). Again, the effect can be explained by opposing pricing strategies of incumbents and entrants.
urn:nbn:de:bsz:180-madoc-409557
Keywords: D43; D83; L11; L13; Q40; 330; Search; Information; Competition; Price Dispersion; Electricity Retail